Who deserves to die : constructing the executable subject - Sarat, Austin; Shoemaker, Karl (University of Massachusetts Press, 2011)
Death penalty scholars "assess the forms of legal subjectivity and legal community that are supported and constructed by the doctrines and practices of punishment by death in the United States. They help us understand what we do and who we become when we decide who is fit for execution."--Back cover.
Keywords: Capital punishment -- Moral and ethical aspects -- United States.; Discrimination in capital punishment -- United States.; Peine de mort -- Aspect moral -- États-Unis.; Discrimination dans l'application de la peine de mort -- États-Unis.; SOCIAL SCIENCE -- Criminology.; Capital punishment -- Moral and ethical aspects; Discrimination in capital punishment; United States